Legislative Policy in Criminalizing Terrorism from a National and International Perspective: (A Comparative And Analytical Study) - Omed Safary Hasan; Majeed Khedher Ahmad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
There is a philosophy behind the punishment which is imposed by legislators for each crime. This research is based on the philosophy of the Iraqi, Kurdistan Region legislators and the international legislators of combating and criminalizing terrorism and its criminal policy in criminalizing terrorism. There are many laws and regulations enacted to protect people and society from terrorism in Iraq and the Kurdistan Region that were issued after the year (2003) due to increase in terrorist acts and the need to combat them with their own laws, and there are also many agreements and decisions at the international level, especially after the events of (11/ September). The criminal policy of the national and international legislators is similar to some extent, because the national legislation of terrorism is strongly affected by international agreements and decisions. The aim of punishment of any criminal that committed a crime in the society is to protect the interest of the society. Therefore, this study attempts to clarify and analyse the protected interests in criminalizing terrorism and combating them by the internal and international legislators. Thus, the internal legislators attempt to protect the society interests, such as protection of life, rights and freedoms, stability of security and system. Furthermore, protection of the environment and the property of the state and citizens is another aim of the legislators. In addition, finding a balance between appropriate punishment and criminalization of the act on the one hand, and the protection of human rights on the other hand could be part of the legislators’ responsibilities. The protected interest and the wisdom of the international legislator in the matter of combating terrorism is more extensive and comprehensive compared to the protected interest in national legislation such as maintaining international peace and security and protecting rights and freedoms.